Structural equation model of poverty - محمود مهدي حسن ألبياتي; مهدي محسن العلاق; وفاء جاسم محمد (Iraqi Journal for Administrative Sciences, 2025)
In this research, many dimensions will be addressed, which represent (health, education, work, and employment). Housing) and introduced several tests to reach the most important of these variables that directly affect poverty, and then Highlight them when developing policies for alleviating poverty. The goal is to define poverty and measure it with a Focus if the process supported by empirical resources and definition